2021
DOI: 10.3390/sym13101914
|View full text |Cite
|
Sign up to set email alerts
|

PrismatoidPatNet54: An Accurate ECG Signal Classification Model Using Prismatoid Pattern-Based Learning Architecture

Abstract: Background and objective: Arrhythmia is a widely seen cardiologic ailment worldwide, and is diagnosed using electrocardiogram (ECG) signals. The ECG signals can be translated manually by human experts, but can also be scheduled to be carried out automatically by some agents. To easily diagnose arrhythmia, an intelligent assistant can be used. Machine learning-based automatic arrhythmia detection models have been proposed to create an intelligent assistant. Materials and Methods: In this work, we have used an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Figure 4 lists the top 10 most relevant authors based on their contributions to arrhythmia research in terms of published articles. The author named U. R. Acharya [31][32][33][34][35], ranks first with five contributions, and S. Dogan [35][36][37][38], contributes four publications. The remaining eight authors contributed equally with three publications.…”
Section: Most Relevant Authorsmentioning
confidence: 99%
“…Figure 4 lists the top 10 most relevant authors based on their contributions to arrhythmia research in terms of published articles. The author named U. R. Acharya [31][32][33][34][35], ranks first with five contributions, and S. Dogan [35][36][37][38], contributes four publications. The remaining eight authors contributed equally with three publications.…”
Section: Most Relevant Authorsmentioning
confidence: 99%
“…Rahul and Sharma [18] suggest a method for classification of heart problem, e.g., Afib atrial fibrillation, Vfib ventricular fibrillation, Vtec ventricular tachycardia, and normal N rhythm, using a hybrid model based on 1-D convolutional neural network (CNN) and bidirectional long short-term memory (Bi-LSTM). Ramkumar et al [19] [20], the authors use the index of PatNet54 charter in order to create an extractor based on a graph. This extractor is known and named as a prism pattern.…”
Section: Related Literature 21 Deep Learning Tasks For Ecg Signal Cla...mentioning
confidence: 99%
“…They only considered seven classes of arrhythmia. In [ 13 ], the authors demonstrated a support vector machine (SVM)-based framework for classifying arrhythmia using a 1D ECG signal. They considered 17 classes of arrhythmia and achieved 97.3% accuracy.…”
Section: Related Workmentioning
confidence: 99%